New research findings on the technical efficiency of village chicken production in Ethiopia, Nigeria, and Tanzania - CGIAR Research Program on Livestock (2021)
The research finding was that the level of technical efficiency was extremely low and heterogenous in the three countries, suggesting enormous opportunities to enhance productivity using available resources, and and transform the traditional subsistence-based production system into a commercially oriented semi-intensive production system.